Effect of River Organic Carbon Input in Mangrove Sediment - Tia Nuraya; Lalu Panji Imam Agawaman (Postgraduate, University of Mataram, 2025)
Mangrove is a coastal ecosystem that absorbs and stores carbon as organic carbon in sediment. The high value of organic carbon in mangrove sediment is influenced by one factor: organic input from the river. This study aims to analyze the effect of the river's total organic carbon (TOC) on TOC stored in mangrove sediment. The samples used were water samples analyzed by the TOC analysis method and sediment samples taken at a depth of 20 cm and analyzed by the combustion method using a C-N analyzer and measuring oceanographic parameters at the research location. The results showed that TOC in the Bakau Kecil River was higher (79 mg/L) compared to TOC in the Bakau Besar River (66.36 mg/L). This is based on the finding of the highest TOC in the Bakau Kecil River mangrove sediment compared to Bakau Besar, with values ​​of 840.14 tons C/ha and 698.86 tons C/ha, respectively. However, regression analysis showed a negative relationship between TOC in mangrove sediment and TOC in waters. If TOC in the river increases, then TOC in sediment tends to decrease. In addition, oceanographic parameters that affect TOC are tides. When TOC rises, TOC is more significant than when TOC recedes.